Pengembangan Media Pembelajaran Berbasis Android Berorientasi Kemampuan Berpikir Kritis Peserta Didik pada Materi Induksi Matematika - Khotimah, Khusnul; Khotimah , Khusnul; Satiti, Wisnu Siwi (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
ABSTRACT The aim of this research is to determine the feasibility of Android-based learning media oriented towards students' critical thinking in mathematics induction material. This research uses the ADDIE development model. The data analysis technique used is quantitative descriptive analysis technique. The results of data analysis from material experts, namely mathematics subject teachers, obtained 90% included in the valid criteria and validation from media experts, namely Mathematics Education Lecturers) obtained 87.5% included in the valid criteria. Meanwhile, in the results of the questionnaire analysis of student responses, it was found that at least 75% or more students responded in the yes category for each aspect responded to which was included in the practical criteria. These results indicate that Android-based learning media is oriented towards students' critical thinking skills in mathematics induction material and is feasible and has received a positive response from students, which means that students are enthusiastic and interested in using Android-based learning media and that Android-based learning media can help students in receive learning materials. KEYWORDS: development, learning media, critical thingking ABSTRAK Tujuan dari penelitian ini untuk mengetahui kelayakan dari media pembelajaran berbasis android beroerientasi berpikir kritis peserta didik pada materi induksi matematika. Penelitian ini menggunakan model pengembangan ADDIE. Teknik analisis data yang digunakan adalah Teknik analisis deskriptif kuantitatif. Hasil analisis data dari ahli materi yaitu dengan guru mata Pelajaran matematika diperoleh 90% termasuk dalam kriteria valid dan validasi ahli media yaitu dengan Dosen Pendidikan Matematika diperoleh 87,5% termasuk dalam kriteria valid. Sedangkan pada hasil analisis angket respon peserta didik diperoleh minimal 75% atau lebih peserta didik merespon dalam kategori iya untuk setiap aspek yang direspon yang termasuk dalam kriteria praktis. Hasil ini menunjukkan bahwa media pembelajaran berbasis android berorientasi kemampuan berpikir kritis peserta didik pada materi induksi matematika layak dan mendapat respon positif dari peserta didik yang berarti peserta didik antusias dan tertarik dalam menggunakan media pembelajaran berbasis android serta media pembelajaran berbasis android ini dapat membantu peserta didik dalam menerima materi pembelajaran. KATA KUNCI: pengembangan, media pembelajaran, berpikir kritis